Estudo de propriedades físicas de cerâmicas do composto multiferroico FeAIO3 - Santos, Guilherme Maia (2012)
Studies concerning magnetoelectric materials, i.e., materials that have (anti)ferroelectric and (anti)ferromagnetic properties in the same phase, has received special attention in the last years. In these materials, as a consequence of the coupling, it could happen the induction of magnetization due to the application of an electric field or the induction of polarization due to presence of a magnetic field. In this work we propose studies of the physical properties of FeAlO3 multiferroic magnetoelectric compound obtained by the high-energy ball milling route and subsequent sintering study. These studies were performed in FeAlO3 pure form and doped with different ions such as La, Mn and Nb. After obtaining the ceramics, studies were made in the sense of how these ions change the physics properties of the compound. The structural, dielectric, ferroelectric and magnetic characterizations were made using the X-Ray diffraction with Rietveld and Le Bail refinements methods, impedance spectroscopy, ferroelectric histereses in a Sawyer-Tower circuit, magnetic measurements were made using a Superconducting Quantum Interference Device (SQUID) and magnetic susceptibility AC. The electrical permittivity curves show in all samples typical behavior of a relaxor material. The hysteresis curves obtained for the ferroelectric samples, saturation has not been achieved because conductivity problems. In the magnetization measurements for each sample were observed changes in the transition temperatures.